Trait neuroticism as a mediator between metacognitions about self-critical rumination and future anxiety in young adults - Damri, Rafi (University of Muhammadiyah Malang, 2026)
Young adults may experience anxiety about their future, which may be related to their tendency to hold metacognitions about self-critical rumination and to neuroticism. However, research examining the dynamics of the relationships among these variables is still limited in Indonesia. This study aimed to examine the influence of metacognitions about self-critical rumination on future anxiety, with neuroticism as a mediator. The study involved 217 participants. Mediation regression analysis was conducted using bootstrapping with 5,000 resamples. The results showed a direct positive relationship between both positive and negative metacognitions about self-critical rumination and future anxiety. In addition, neuroticism mediated the relationships between positive and negative metacognitions about self-critical rumination and future anxiety. The limitations of this study include the relatively small sample size, limited socio-demographic diversity, and suboptimal cross-cultural evaluation of the positive metacognitions about self-critical rumination scale. Therefore, future research is recommended to replicate this study using a larger and more diverse sample and to strengthen the instrument’s cross-cultural validation.